Intention to buy eco- friendly packed product among Malaysian - Loo, Meng Jun (2023)
The objective of this research is to investigate the intention of Malaysians to purchase eco-friendly packed products, using a causal research approach to determine any cause-and-effect relationships between independent variables (Attitude, Subjective Norm, and Perceived Behavioral Control) and the dependent variable (Purchase Intention). A total of 400 questionnaires were distributed via Google Forms to residents who are lived in Penang, Malaysia, and data analysis was carried out using IBM SPSS software. Descriptive analysis, reliability testing, Pearson Correlation Coefficient Analysis, and Multiple Linear Regression were applied to interpret the collected data. The study findings indicated that Purchase Intention was influenced by Attitude, Subjective Norm, and Perceived Behavioral Control. However, there were certain limitations to this research, which will be further discussed in subsequent chapters, along with recommendations for future research